Socio-labor factors associated with the quality of life at work of the nursing professional who works in a private clinic, Lima, 2020 - Adanaqué Castillo, Jaqueline (2020)
Objective: to determine the socio-labor factors associated with the quality of life at work of the nursingprofessional who works in a private clinic in Lima. Methodology: It is a quantitative, correlational, crosssectionalstudy. The selection of the sample was made through non-probability sampling for convenienceand was made up of 109 nursing professionals. To collect data on socio-labor factors, a questionnaireprepared by the researchers was used and, to measure quality of life, the questionnaire “CVT-GOHISALO”proposed by, Pando, González, Aranda and Elizalde (2017) was used. Results: 76.1% of the nursingprofessionals present Average quality of life at work, 16.5% high, and 7.3% low. Regarding the associationof socio-labor factors and quality of life at work, it is found that 39.4% with low social support have lowquality of life, 26.6% with high social support have high quality of life; 50.5% with high discrimination havea low quality of life, 18.3% who do not suffer discrimination have a high quality of life; 56% who receivelow remuneration have low quality of life, 16.5% who receive high remuneration have high quality of life; 62.4% with poor employment conditions present low quality of life, 20.2% with optimal employmentconditions present high quality of life; 43.1% who perceive a poor work environment have a low qualityof life, and 24.8% who perceive an optimal work environment have a high quality of life. The socio-laborfactors that have the highest association with quality of life at work are: discrimination and employmentconditions with OR = 4,672 and OR = 9,087 respectively. Conclusion: there is a significant associationbetween socio-labor factors and the quality of life in the work of nursing professionals.